(untitled) (Scientific journal of the Fergana State University, 2023)
The article compares Hamza’s "Uzbek Women" with Ghazi’s predecessors, such as Amiriy and Fazli, with the same weight, radif, rhyme, and artistic ghazals, and shows that it is a completely new work written by Fazli’s introduction to Ghazi.